The impact of out-the-window size on air traffic controllers' visual behaviours and response time on digital tower operations. Issue 166 (October 2022) - Li, Wen-Chin; Moore, Peter; Zhang, Jingyi; Lin, John; Kearney, Peter
Highlights: Panoramic display size affects controller's visual behaviours and their response time on target identifications. Larger screen induced bigger visual distortion and led to larger ranges of head and eyes movements. Results demonstrated that the 43-inch display is a better HMI design than 55-inch OTW panorama display. System designers must consider the effects of peripheral vision and visual distortion on panoramic displays on digital tower operations. Abstract: Digital tower using video-panorama display permits the provision of air traffic services remotely without the need for a local physical tower. The recent growth of visual science has demonstrated the popular concept in respect of the size of display "bigger is better". The aim of this research is to examine the sizes of Out-the-Window (OTW) panoramic displays and how they affect controller's visual behaviours, response time and workload. There are two validated OTW (43-inch vs 55-inch) which can potentially be implemented in the digital tower module. It is critical to investigate air traffic controllers' cognitive demand and monitoring performance while interacting with different sizes of OTW in the digital tower module. This research recruited 15 qualified controllers working at a European regional airport. The results demonstrated that a 43-inch display was a better human-computer interaction in target identification than a 55-inch OTW panorama display. The subjective and objective approaches revealed that controllers' visual behaviours and response times were difference while interacting with different sizes of OTW, but controllers' workload did not show difference. The bigger screen presents bigger stimuli which are easier spotted by ATCOs, but it induces bigger amplitude of head and eye movements, bigger distortion on both edges of screen and longer response time on target identifications. System designers should be aware of the effects of peripheral vision and visual distortion on panorama displays while designing digital tower modules for the provision of future air traffic services. Graphical abstract: Image, graphical abstract